Comparative double and integer optimization of low-grade heat recovery from PEM fuel cells employing an organic Rankine cycle with zeotropic mixtures. (15th January 2021) - Fakhari, Iman; Behzadi, Amirmohammad; Gholamian, Ehsan; Ahmadi, Pouria; Arabkoohsar, Ahmad
Highlights: A PEM fuel cell integrated with an ORC using twenty zeotropic mixtures is proposed. Considering mixture type as a variable, a newly optimization mode is applied. Comparative single/multi optimizations are performed to find the optimal mixtures. Low-temperature PEM fuel cell works better from multi-objective optimization facet. (13.32/86.68) R601a/Hexane is the best fluid from multi-objective aspect. Abstract: In the present study, a comparative optimization analysis of a hydrogen-based proton exchange membrane (PEM) fuel cell integrated with an organic Rankine cycle (ORC) using twenty different zeotropic mixtures is accomplished. Accordingly, considering the mixture type as a qualitative decision variable, a novel method of integer single/multi-objective optimization is implemented from thermodynamic and economic aspects. Using a developed genetic algorithm code in MATLAB software, histogram and scatter distributions are presented to determine the density of optimum points and optimum fraction for each mixture. The optimal solution points of exergy efficiency and total cost rate for each mixture are extracted via a Pareto frontier diagram. Eventually, to assess the influence of major decision variables on system performance, a comparative parametric study on five optimal mixtures is carried out. Referring to single-objective optimization results of the ORC unit and the overall system, the use of R601/Cis-2-Butene (2/98) and R601a/Cis-2-Butene (1.32/98.68), respectively, lead to the highest exergy efficiency. Also, considering exergy efficiency as objective, the results of optimization indicates that at optimal condition, the temperature difference between the PEM fuel and evaporator temperature is 13 K. Results further indicate that while a high-temperature PEM fuel cell is a suitable option from an exergy maximization aspect, a low-temperature PEM fuel cell is superior from multi-objective optimization viewpoint. Results of multi-objective optimization reveal that R601a/Hexane (13.32/86.68) and R601a/C-2-Butene (20.14/79.86) are the best mixtures. Furthermore, what stands out from scatter distribution is that most of the optimal points of evaporator temperature are between 305 K and 380 K. Comparative parametric study results demonstrate that in the selected range of major decision variables, R601a/Cis-2-Butene (20.14/79.86) and R601a/Hexane (13.32/86.68) are the best optimum mixtures from an economic facet.